Pengaruh Komitmen, Kompetensi, dan Locus of Control Terhadap Kinerja Pegawai Pemerintahan - Dudi, Alwa; Moeins, Anoesyirwan; Elfiswandi (Jurnal Informatika Ekonomi Bisnis, 2019)
The aim of this study is the level of influence of commitment on employee performance in several Regional Apparatus Organizations (OPD). The method used is a survey with an associative type. The processed data is questionnaire filling data for all Civil Servants (PNS) in the Solok City Regional Government, totaling 158 people. The results of this study are that commitment has a significant effect, competition has no significant effect, and Locus of Control has a significant effect on employee performance. So the leadership of several OPDs continues to pay attention to the commitment and Locus of Control of each employee to improve employee performance.